The Effect of Salinity Stress on the Germination and Early Growth Parameters of Selected Ryegrass Species - Özkan, Şükrü Sezgi; Özkan, Esra Çetinkaya (My University, 2025)
Ryegrass (Lolium sp.) species are widely utilized in turfgrass areas worldwide due to their rapid establishment, aesthetic appeal, and adaptability to various environmental conditions. Salt stress is a significant environmental factor that adversely affects the growth and development of turfgrass species; this situation particularly threatens the health and performance of turfgrasses during the germination phase. The objective of the study was to evaluate the germination and early growth parameters of four different ryegrass species (annual ryegrass “Lolium multiflorum” cv. Axcella, diploid perennial ryegrass “Lolium perenne” cv. Sun, tetraploid perennial ryegrass “Lolium perenne” cv. Tetragreen, and intermediate ryegrass “Lolium hybridum” cv. TransAm) under different salinity stress levels (0, 2.5, 5.0, 7.5, 10.0, 12.5 g L?¹ sodium chloride-NaCl). In the study, germination rate (%), shoot and root length (cm), shoot and root fresh weight (mg), vigor index, salt tolerance index (%), and thousand-seed weight (g) parameters were determined. According to the results, salinity stress levels had significant effects on all treatments. The selected ryegrass species demonstrated better growth under a salinity stress level of 2.5 g L-1 than the control. However, as the salt concentration increased, significant declines were observed in both germination and early growth, starting at 7.5 g L-1. Among the species, annual ryegrass cv. Axcella exhibited better performance under salinity stress. Additionally, the correlation coefficient results indicated a positive and significant correlation among all parameters, except for those involving the thousand-seed weight.
Keywords: Salinity; correlation; germination; Turfgrass; thousand-seed weight